Efficient method for molecular characterization of the 5' and 3' ends of the dengue virus genome (2020)
Dengue is a mosquito-borne disease that is of major importance in public health. Although it has been extensively studied at the molecular level, sequencing of the 5' and 3' ends of the untranslated regions (UTR) commonly requires specific approaches for completion and corroboration. The present study aimed to characterize the 5' and 3' ends of dengue virus types 1 to 4. The 5' and 3' ends of twenty-nine dengue virus isolates from acute infections were amplified through a modified protocol of the rapid amplification cDNA ends approach. For the 5' end cDNA synthesis, specific anti-sense primers for each serotype were used, followed by polyadenylation of the cDNA using a terminal transferase and subsequent PCR amplification with oligo(dT) and internal specific reverse primer. At the 3' end of the positive-sense viral RNA, an adenine tail was directly synthetized using an Escherichia coli poly(A) polymerase, allowing subsequent hybridization of the oligo(dT) during cDNA synthesis. The incorporation of the poly(A) tail at the 5' and 3' ends of the dengue virus cDNA and RNA, respectively, allowed for successful primer hybridization, PCR amplification and direct sequencing. This approach can be used for completing dengue virus genomes obtained through direct and next-generation sequencing methods. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.